Fostering Diversity Awareness in Indonesian Islamic Boarding Schools: Cross-Cultural Religious Literacy-Based Approach in Teaching English - Idman, Muhajirah (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Indonesia faces the challenges of intolerance and limited interfaith understanding despite its religious and cultural diversity. This study explores the integration of Cross-Cultural Religious Literacy (LKLB) in English teaching within pesantren to enhance students' diversity awareness. Pesantren, as traditional Islamic educational institutions, have an important influence on young Muslims' perspectives and can potentially promote interfaith harmony. English, as a lingua franca, facilitates access to diverse cultures and religions. The LKLB approach develops three competencies: personal (understanding one's own religion), comparative (understanding other religions), and collaborative (working with people of other faiths). This study aims to examine how Cross-Cultural Religious Literacy (LKLB) can be integrated into English teaching, how students respond to such instruction, and what pedagogical implications emerge from its implementation. This study is significant as it addresses the gap between religious moderation discourse and classroom-level pedagogical practice in faith-based education. Using an ethnographic approach, this research addresses three questions: (1) How is cross-cultural religious literacy integrated into English teaching in pesantren? (2) How do students respond to LKLB-based English instruction regarding their awareness of religious and cultural diversity? (3) What pedagogical implications emerge from implementing LKLB in English teaching? The findings demonstrate that LKLB-based English instruction fosters students’ empathy, self-reflection, respect, and openness towards religious and cultural diversity. It contributes theoretically by widening religious literacy in ELT and pedagogically by offering a practical model for LKLB-based English instruction.